The relationship between motivation and level of job performance among support staff in public sector organization in Bandar Temerloh, Pahang / Alyna Aida Mohamed Noor and Nor Hidayah Othman - Mohamed Noor, Alyna Aida; Othman, Nor Hidayah (2012)
The purpose of this research was to investigate the relationship between motivation and level of job performance among support staff in public sector organization in Bandar Temerloh, Pahang. This correlational research used a stratified disproportionate sampling technique and the sample size was determined using the Krejcie and Morgan (1970) sample size table. Questionnaires were distributed to 186 respondents who work as support staff in selected organization, adopted from Rigsrevisionen's Employee Performance Review "Interview Questionnaire", Science Motivation Questionnaire and Intrinsic Motivation Inventory Questionnaire. The response rate was 64.52%. The questionnaires were analyzed using SPSS version 18 to determine the result. The findings show that there was a strong relationship between motivation and level of job performance (r=0.552, p=0.01). Other than that, motivation does improve job performance, r=O.475 for intrinsic and r=0.492 for extrinsic. There is moderate level of job performance, (Mean=4.1708) and the majority of the respondents believed that extrinsic motivation (position, salary, and reward) is the major factors that contributed to their level of job performance, r=0.492. It is recommended that employee should seek what factors that can motivate them and employers should offer extrinsic motivation. Future research should study top management or middle management, take larger number of respondents, find other factors that can influence the level of job performance and conduct in different setting. It will be interesting to compare the differences of level of job performance between various levels of management in an organization.